Analisis e-book IPA kelas IX SMP berdasarkan pada aspek literasi bencana - Radha Firaina; Mu’tia Faizah Apriani; Rif’il Husniyah; Asrizal Asrizal (Universitas Negeri Padang, 2019)
Indonesia is famous as one of the countries prone to natural disasters. The negative impact is the loss of lives and property so that it becomes a very crucial problem in Indonesia. On the other side, this natural disaster can be used as a learning resource that is utilized. This disaster literacy is expected to be present in every learning resource that is designed as teaching material at each level of the education unit. therefore, it is necessary to know the extent to which disaster literacy has been contained in teaching materials that have been used by students in schools. The purpose of this research was to determine the feasibility of five books of IX grade 2 ninth grade junior high school in terms of disaster literacy. This research is a descriptive research that obtained data through a questionnaire. This research is focused on analyzing the components of knowledge about disasters which are broken down into five research indicators. From each indicator, an average score of five E-books is obtained and expressed as a percentage and displayed graphically. The results of this research indicate that of the five E-books analyzed, E-books 4 and E-books 5 are in the range of percentages between 55% to 65% so that they are categorized quite well, while E-books 1, E-books 2 and E-books book 3 is in the range of 40% to 54% so that it is categorized as not good.